Perception of repeat purchase intent on consumer satisfaction of junk food J.CO donuts & coffee and dunkin donuts - Surya Bintarti; Ergo Nurpatria Kurniawan; Joni Heruwanto (Jurnal Ekonomi, 2024)
Sales promotion can play a role in strengthening the perceived value as a form of quality experience for consumer repurchase intentions for J.CO Donuts & Coffee brand products and also for Dunkin Donuts brand products, because the relationship between sales promotion can strengthen the relationship between perceived value to repurchase intent where attractive promos are given coupled with the taste value of J.CO Donuts & Coffee brand products and also good Dunkin Donuts It is likely to increase consumer intent to make repurchases. Sales promotion carried out can moderate the price set to encourage consumers to repurchase J.CO Donuts & Coffee brand products, this is because the price of J.CO Donuts & Coffee is in accordance with the quality of its bakery products and promotional activities delivered to consumers. However, this condition is not the same as the condition of Dunkin Donuts brand donut products where sales promotion does not have a direct role in repurchase intentions so that it cannot strengthen the price relationship with Dunkin Donuts consumer repurchase intentions, this is because some consumers do not always follow Dunkin Donuts product promos and the promos carried out are not always there.